Pelatihan Pembuatan Pupuk Organik Cair Kepada Kelompok Tani Di Desa Sepawon, Kecamatan Plosoklaten, Kabupaten Kediri - Tanjungsari, Ardina; Andaruisworo, Sapta; Yuniati, Erna; Solikin, Nur; Anifiatiningrum; Irawan, Hebi (Universitas Nusantara PGRI Kediri, 2023)
Liquid Organic Fertilizer (LOF) is a liquid textured fertilizer resulting from the fermentation of various organic materials. Making and applying LOF is relatively easy, it is needed in small quantities and the high nutrient content is quickly utilized by plants. This activity aims to provide training in making POC to the Sepawon Village Farmers Group, Plosoklaten District, Kediri Regency to increase agricultural and plantation productivity, alternative to the scarcity of synthetic fertilizers, and utilization of surrounding waste. The method used by the Participatory Rural Approach (PRA) is education of knowledge to the community through training, practice and mentoring. Ingredients for making 1 kg beef rumen POC, 1 L coconut water, 1 L rice washing water, 1 L rabbit urine, 1 kg banana peel, and molasses. The materials for making POC can be adapted to agricultural, plantation and livestock waste in Sepawon Village, so it can increase the economic value of Farmer Groups.